Synthesis of Carboxymethyl Cellulose from Nypa fruticans for Coating Metformin on Zn-Based Metal-Organic Framework Nanohybrid as a Bionanocomposite Drug Delivery System - Delviani, Delviani; Maharani, Viola Giary Rizkillah; Shadrina, Putri Nur; Warni, Tri; Azizah, Regina Wan; Tarigan, Indra Lasmana; Latief, Madyawati (Makara Journal of Science, 2025)
Diabetes is a common and rapidly spreading disease that affects 6.6% of the world’s population. Metformin hydrochloride (HCl) is an effective oral pharmacological treatment for type 2 diabetes mellitus (T2DM) patients because of its capability to reduce glucose levels and the risk of hypoglycaemia. However, gastrointestinal sensitivities to this drug can cause diarrhoea, nausea, vomiting and stomach ache. An alternative is controlled release technology by coating metformin with carboxymethyl cellulose (CMC) and zinc-metal-organic framework (Zn-MOF) through the encapsulation method. Therefore, this study aimed to coat metformin formulations using CMC in a Zn-MOF to control release into the body and minimise the side effects related to doses. The results showed that CMC/metformin@Zn-MOF encapsulation had a controlled blood sugar lowering effect and stable healing effectiveness even at a low concentration of 1:10 of local metformin. In vitro, the released concentrations from local metformin tablets and CMC/Metformin@Zn-MOF were 199.50 ppm of 500 ppm and 42.182 ppm of 50 ppm, with release percentages of 39.90% and 84.364%, respectively. This study found that metformin masking using CMC and Zn-MOF maximally produced a modified release formula along the intestine by reducing the concentration to increase tolerability in lowering blood sugar effectively for T2DM patients with minimal side effects.